Biosorption of heavy metals: new perspectives - Tavares, T. (2012)
Biosorption, the ability of certain materials of biologic origin to entrap metal ions, is a natural process that may be seen as xenobiotic or may be used through technological processes to recover or remediate contaminated ecosystems. This process is known to be very appropriate to remediate liquid effluents with low metal ions concentrations. In the last four or five decades, very interesting publications have been presenting useful applications of biosorption systems aiming the sustainability of some industrial processes, known for sending into the environment huge amounts of heavy metals, contaminating soils, water, air, flora and fauna. Relevant research work has been done using different biosorbents and optimizing operation procedures. Several industrial processes are patented and working effectively for quite a long time. Many good and exhaustive reviews, covering all possible adsorbents, adsorbates and operational parameters, are easily accessible and even this year a couple of them have been presented to the scientific community. In this chapter devoted to biosorption, the applications of biosorption are presented with a new perspective: an integrated system, associating metal entrapment, biological chemical reduction, ion exchange and environmental oxidation catalysis in liquid and in gas phase. The metal residues of some industries are now converted into high value catalysts to be used in mild oxidation of volatile organic compounds, reusing expensive and contaminating metals in the whole industrial activity. Biosorption allows the retention of the metallic ions present in liquid solutions and special attention is paid to hexavalent chromium as it is usually present in the anionic status, making uninteresting for ion-exchange in zeolites, the biomass supports herein presented. The biomass selected for performing biosorption is also able to reduce hexavalent chromium to its trivalent form, which is cationic. Now, the ion exchange within the zeolites is feasible, and the new matrices with the entrapped ions may be used downstream in environmental catalysis. In fact, these so prepared catalysts proved to be more selective towards the degradation of volatiles into C02 than the expensive palladium catalysts. Cr catalysts may be used, as they are, in gaseous phase reactions or may be subject to a pre-treatment with ligants to fix the metal ions inside the zeolitic structure, avoiding the eventual leaching in liquid phase reactions. This chapter aims, in resume, to enlarge the applications of biosorption in an integrated and sustainable procedure, indicating new ways of using microorganisms able to sorb as well as to change the chemical nature of metal ions, of using cationic ion-exchangers to retain original negative ions and of raising the market value of industrial residues by substitution of very expensive environmental catalysts. © 2012 Scrivener Publishing LLC. All rights reserved.